Kibernetinis persekiojimas (cyberstalking): viktimizacijos ypatumai ir teisinio reagavimo galimybės - Panomariovaitė, Gabija; Zokaitė, Justina (Vilnius University Open Series, 2021)
In the article, the phenomenon of cyberstalking is presented through the differentiation from convenient stalking (stalking without the usage of cyberspace). Moreover, cyberstalkers and their victims are characterised by distinguishing their prevalent features and interaction. Authors discuss national as well as international measures of legal response to cyberstalking crimes.